2016
DOI: 10.3390/md14120229
|View full text |Cite
|
Sign up to set email alerts
|

Kunitz-Type Peptide HCRG21 from the Sea Anemone Heteractis crispa Is a Full Antagonist of the TRPV1 Receptor

Abstract: Sea anemone venoms comprise multifarious peptides modulating biological targets such as ion channels or receptors. The sequence of a new Kunitz-type peptide, HCRG21, belonging to the Heteractis crispa RG (HCRG) peptide subfamily was deduced on the basis of the gene sequence obtained from the Heteractis crispa cDNA. HCRG21 shares high structural homology with Kunitz-type peptides APHC1–APHC3 from H. crispa, and clusters with the peptides from so named “analgesic cluster” of the HCGS peptide subfamily but forms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(81 citation statements)
references
References 80 publications
1
73
0
1
Order By: Relevance
“…Indeed, it was shown that the outer pore region of TRPV1 plays a critical role in channel gating (13,24,26,(38)(39)(40)(41). This domain was further found to be involved in channel inhibition by several animal toxins and monovalent cations (26,42,43). Accordingly, perturbations to the structure of the outer pore region were reported to contribute to the low TRPV1 unitary conductance elicited by protons (44).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was shown that the outer pore region of TRPV1 plays a critical role in channel gating (13,24,26,(38)(39)(40)(41). This domain was further found to be involved in channel inhibition by several animal toxins and monovalent cations (26,42,43). Accordingly, perturbations to the structure of the outer pore region were reported to contribute to the low TRPV1 unitary conductance elicited by protons (44).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 55 potential toxins were predicted based on the genome but only 12 FIGURE 1 | Phylogenetic tree representing the phylum Cnidaria based on previous descriptions (Bridge et al, 1992(Bridge et al, , 1995Berntson et al, 1999;Marques and Collins, 2004;Collins et al, 2006;Daly et al, 2007;Jimenez-Guri et al, 2007;Feng et al, 2014;Zapata et al, 2015) and showing the relationship of organisms discussed in this mini-review. Monastyrnaya et al (2016). b Diochot et al (2004), Moreels et al (2017).…”
Section: Scleractinia (Stony Coral)mentioning
confidence: 99%
“…1). Полученной экспрессионной конструкцией трансформировали клетки E. coli штамма BL21(DE3) ("Novagen", Германия) и проводили гетерологичную экспрессию в оптимизированных условиях [10,11].…”
Section: биохимия биофизика молекулярная биологияunclassified